Design of the dynamic reference asynchronous analog-to-digital converter - Wirodjojo, Wendy Riyanti (2019)
Dynamic reference analog-to-digital converter (ADC) is a type of ADC that samples the input in parallel and determines the output using a binary search algorithm. In this project, an 8-bit dynamic reference ADC is designed using 0.18µm CMOS technology. The design will be implemented to convert a continuous input signal ranging from 0 to 1V into an 8-bit discrete signal represented by the ground (bit 0) and supply voltage of 1.8V (bit 1). The overall circuit of this project will be designed using Cadence Virtuoso Schematic Editor and simulated in Cadence Virtuoso Analog Design Environment. The building block of the proposed ADC will consist of several components including voltage reference, voltage comparator, and digital-to-analog converter (DAC).